Organizacja i dyslokacja jednostek bojowych w Łódzkim Okręgu Wojskowym po przejściu na stopę pokojową (sierpień 1945 r. – listopad 1946 r.) - Jarno, Witold (Przegląd Nauk Historycznych, 2013)
The article describes the organization and dislocation combat units subordinated undertakings command of Military District of Łódź, after the transition to peace organizations in September 1945. Initially, the most of them were 1 Training Division, which was renamed the 18 Infantry Division and moved to Bialystok in Warsaw Military District in November 1945. In its place, in September 1945 to the Łódź Military District transferred 2 Infantry Division, which had its garrisons in Częstochowa, Kielce, Piotrków Trybunalski and Radom. In addition, the Łódź Military District stationed several units of other weapons, such as: 1. Motorized Infantry Brigade in Łódź (disbanded in early 1946), 14. Anti-tank Artillery Brigade and 21. Reserve Artillery Regiment (created based on the Heavy Artillery Regiment 82. in Tomaszów Mazowiecki), 52. Self-propelled Artillery Regiment in Zgierz, 2. Brigade Engineer in Radom (in the summer of 1946 moved to the Warsaw Military District), 3. Communications Regiment in Zgierz (reorganized in the autumn of 1945 the 1st Regiment of Communications) and 2. Battalion Flamethrowers in Skierniewice. In the district stationed many units of the Air Force, which however, were subordinate directly to the Polish Army Aviation Command. Because of financial savings, the Łódź Military District was disbanded on the 30th of November 1946, however combat units which stationed on the territory of this district were subordinated to the commanders of other military districts.